Carbon nanothreads enable remarkable enhancement in the thermal conductivity of polyethylene. Issue 14 (6th April 2021) - Zhan, Haifei; Zhou, Ying; Zhang, Gang; Zhu, Jihong; Zhang, Weihong; Lü, Chaofeng; Gu, Yuantong
Abstract : Polymer nanocomposites with regularly aligned and evenly distributed carbon nanothreads exhibit better thermal conductivity than their counterparts with randomly dispersed nanofillers or nanofillers with functional groups. Abstract : Polymer nanocomposites with high thermal conductivity have been increasingly sought after in the electronic industry. Based on molecular dynamics simulations, this work assesses the thermal transport in polyethylene (PE) nanocomposites with the presence of a new one-dimensional nanofiller–a carbon nanothread (NTH). It is found that the axial thermal conductivity of PE nanocomposites increases linearly with the content of regularly aligned NTH fillers, while the aggregated pattern suppresses the enhancement effect. This phenomenon is explained by a stronger filler–filler interaction that reduces the intrinsic thermal conductivity of the NTH. Results show that the randomly dispersed NTHs can hardly promote heat transfer because effective heat transfer channels are lacking. Strikingly, surface functionalization has an adverse effect on the thermal conductivity due to the presence of additional voids. The presence of voids answers a long-standing open question that functionalization of the heat conductive filler only slightly improves the thermal conductivity of the polymer composite. Additionally, the transverse thermal conductivity degrades in the presence of the NTH and exhibits no clear correlation with the filler content or the distribution pattern. Overall, this study provides an in-depth understanding of the heat transfer within the polymer nanocomposites, which opens up possibilities for the preparation of highly conductive polymers.